GROSS PREMIUM INCOME AND CLAIMS SETTLEMENT FOR FIRE INSURANCE POLICY IN NIGERIA: A PANEL APPROACH - Akindipe, Leke Ebenezer; Isimoya, ogorchukwu Augustine (Annals of Spiru Haret University. Economic Series, 2022)
ABSTRACT Claims, being the heartbeat of the workability of insurance, are the most critical contact influencer between the insuring public and the insurer. It serves as a critical path to truth that shapes the policyholders’ ultimate perceptions of their insurers. This study evaluated the relationship between gross premium income and claims settlement with specific focus on fire insurance business in the Nigerian insurance industry from 2010 to 2021. Data on gross premiums income and gross claims paid over the period were extracted from Nigerian Insurers Association (NIA) annual reports and digest. Stationarity test carried out on the data revealed that data is stationary at the 1%, 5% and 10% levels of significance. Using the ordinary least squares regression, the calculated probability value of 0.0000 is lower than the 0.05 significant value, which shows that there is a significant significance of the data. The computed linear co-efficient of determination (R2= 0.928731) shows that 92.87% of the total return on asset is accounted for by the independent variables which are expense ratio and net claims. It was therefore concluded that there is a significant relationship between gross premium income and gross claims payment of fire insurance in careful consideration must be given to other administrative costs, such as underwriting, which have the potential to reduce the Revenues and profits of the company